Implementing Open Dialogue approaches: A scoping review. Issue 4 (28th July 2021) - Buus, Niels; Ong, Ben; Einboden, Rochelle; Lennon, Elizabeth; Mikes‐Liu, Kristof; Mayers, Steven; McCloughen, Andrea
Abstract: Open Dialogue approaches fall broadly into the area of systemic psychotherapeutic practices. They encourage active participation of families and social networks, and emphasize genuine collaboration within highly integrated systems of health‐care service delivery. These approaches are currently being implemented in a growing number of services across the globe, and in this review, we summarize and discuss insights from papers concerned with the implementation of Open Dialogue. We used a scoping review method, which included systematic literature searches and summarizing data extraction as well as consultation with eight Open Dialogue implementation stakeholders who were invited to comment on preliminary review findings and a draft paper. We included 18 studies in the review and present their content under four thematic headings: 1. Training, 2. Family and network experiences, 3. Staff members' experiences, and 4. Structural and organizational barriers and resistance to implementation. In general, the studies did not include rich descriptions of the implementation contexts, which made it difficult to draw conclusions across studies about effective implementation practices. The discussion draws on Jamous and Peloille's (Professions and professionalisation, 1970, Cambridge University Press, 109‐152) concepts of "indeterminacy" and "technicality, " and we argue that the indeterminacy that dominates Open Dialogue is a challenge to implementation efforts that favor specific and standardized practices. We conclude by encouraging the development of implementation initiatives that theorize Open Dialogue practices with higher levels of technicality without corrupting the fundamental spirit of the approach. Resumen: Los métodos de diálogo abierto (Open Dialogue) pertenecen ampliamente al área de las prácticas psicoterapéuticas sistémicas. Estos fomentan la participación activa de las familias y los contactos sociales, y enfatizan la colaboración genuina dentro de los sistemas sumamente integrados de prestación de servicios de asistencia sanitaria. Estos métodos se están implementando actualmente en un número cada vez mayor de servicios en todo el mundo y, en esta revisión, resumimos y debatimos los conocimientos obtenidos de artículos relativos a la implementación del diálogo abierto. Utilizamos un método de revisión exploratoria, que incluyó búsquedas sistemáticas de publicaciones y resúmenes de extracción de datos, así como consultas con ocho partes interesadas en la implementación del diálogo abierto, a quienes se las invitó a comentar sobre los resultados preliminares de la revisión y sobre un borrador del artículo. Incluimos 18 estudios en la revisión y presentamos su contenido en cuatro títulos temáticos: 1. Capacitación, 2. La familia y las experiencias de contacto social, 3. Las experiencias de los miembros del personal, y 4. Los obstáculos estructurales y organizativos y la resistencia a la implementación. En general, los estudios no incluyeron descripciones valiosas de los contextos de implementación, lo cual dificultó la posibilidad de sacar conclusiones entre los estudios con respecto a las prácticas eficaces de implementación. En el debate se utilizan los conceptos de "indeterminación" y "tecnicidad" de Jamous y Peloille's (1970), y argumentamos que la indeterminación que domina el diálogo abierto supone un desafío para los esfuerzos de implementación que favorecen prácticas específicas y estandarizadas. Finalizamos fomentando el desarrollo de iniciativas de implementación que teorizan las prácticas de diálogo abierto con niveles más altos de tecnicidad sin alterar el espíritu fundamental del método. 摘要: 开放式对话方法大致属于系统性心理治疗实践的范畴。它们鼓励家庭和社会网络的积极参与，并强调在高度整合的卫生保健服务系统内的真正合作。这些方法目前正在全球范围内越来越多的服务中实施。在这篇综述中，我们总结并讨论了有关开放对话实施的论文中的见解。我们采用了范围审查的方法，包括系统的文献搜索和总结数据提取，以及咨询8个开放对话实施的利益相关者，他们被邀请对初步审查结果和论文草案发表意见。我们在综述中纳入了18项研究，并在四个主题下介绍其内容。1. 培训；2.家庭和网络经验；3.工作人员的经验；4.结构和组织上的障碍及执行上的阻力。总的来说，这些研究没有包括对实施环境的丰富描述，这使得我们很难在不同的研究中得出关于有效实施做法的结论。讨论借鉴了Jamous和Peloille（1970）的 "不确定性 "和 "技术性 "的概念，我们认为主导开放对话的不确定性是对倾向于具体和标准化实践的实施努力的挑战。我们的结论是鼓励发展具体执行的举措，在不破坏该方法的基本精神的情况下，以更高的技术性水平理论化开放对话实践。